2017
DOI: 10.1002/2017gl074511
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Seismic Fields of Hydraulic Jumps at Varying Froude Numbers

Abstract: Mechanisms that produce seismic and acoustic wavefields near rivers are poorly understood because of a lack of observations relating temporally dependent river conditions to the near‐river seismoacoustic fields. This controlled study at the Harry W. Morrison Dam (HWMD) on the Boise River, Idaho, explores how temporal variation in fluvial systems affects surrounding acoustic and seismic fields. Adjusting the configuration of the HWMD changed the river bathymetry and therefore the form of the standing wave below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…The topography of the Las Lajas drainage just north of the FG13 array, before the channel widens, is hilly and complex (Figure 9), with moderate slope, possible rapids and fast-moving flow. It is also prudent to note that just north of FG13, where most of the array's coherent infrasound originates, sudden widening of the river channel and probable hydraulic jump could account for a disproportionate share of both seismic and acoustic power at station FG13 [Figure 9B-E Ronan et al 2017;Marchetti et al 2019]. Without visual ground truth, however, it is hard to say whether these flow behaviors occurred during this lahar event.…”
Section: Flow Evolution From Fg12 To Fg13mentioning
confidence: 99%
“…The topography of the Las Lajas drainage just north of the FG13 array, before the channel widens, is hilly and complex (Figure 9), with moderate slope, possible rapids and fast-moving flow. It is also prudent to note that just north of FG13, where most of the array's coherent infrasound originates, sudden widening of the river channel and probable hydraulic jump could account for a disproportionate share of both seismic and acoustic power at station FG13 [Figure 9B-E Ronan et al 2017;Marchetti et al 2019]. Without visual ground truth, however, it is hard to say whether these flow behaviors occurred during this lahar event.…”
Section: Flow Evolution From Fg12 To Fg13mentioning
confidence: 99%
“…The spectral characteristics and timing of these events are consistent with wind-generated noise (e.g., Withers et al, 1996), a well known and common issue for infrasound sensors that are not equipped with strong wind filters Journal of Geophysical Research: Earth Surface 10.1002/2017JF004295 (e.g., Hedlin & Alcoverro, 2005). Recent experimental work utilizing an adjustable hydraulic jump has suggested supercritical flow in fluvial systems, such as that occurring in whitewater rapids and waterfalls, may be necessary for flowing water to produce strong infrasound signals (Johnson et al, 2006;Ronan et al, 2017). During our study period, the dominant flow regime is subcritical and the generation of infrasound signals was clearly limited.…”
Section: Infrasound Spectral Analysismentioning
confidence: 99%
“…The historic events at Kilauea Volcano in 2018: summit collapse, rift zone eruption, and Mw6.9 earthquake 2015; Toney et al 2021), debris flows (Schimmel and Hübl 2016;Marchetti et al 2019), lahars (Johnson and Palma 2015), pyroclastic flows (Ripepe et al 2010), and fluvial processes (Schmandt et al 2013;Ronan et al 2017). Observations of lava flow infrasound, however, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…A flow in a supercritical state will produce a hydraulic jump whenever the flow or channel characteristics are favorable. Ronan et al (2017) studied controlled fluvial hydraulic jumps and found that infrasound began to be produced when waves transitioned from nonbreaking undular jumps to breaking weak jumps at Fr values above 1.7. Similar results were observed in seismoacoustic data from whitewater river rapids (Schmandt et al 2013).…”
Section: Introductionmentioning
confidence: 99%